Qualidade de vida de idosos residentes em instituições de longa permanência no município de Belo Horizonte - Jucilene Carneiro Moreira (2017)
Aging is a growing global phenomenon requiring the development of public policies that promote a healthy aging, with autonomy and independence. The growth of the elderly population implies profound social pressures, mainly for pension systems, health and Social services. The nursing home residents, of Social Assistance aims to welcome people to infringe rights, for the purpose of full protection and includes the hosting in long-stay Institution for elderly. Belo Horizonte has 22 associated with municipal power nursing home residents and ability to accommodate up to 890 elderly people, of both sexes, with varying degrees of dependence. This study seeks to evaluate the quality of life (QOL) of institutionalized elderly. This is a cross-sectional study, with primary and secondary data analysis. We used data from the Information System and management of social policies, CENSO SUAS 2016 and information obtained by the application of validated instruments-Katz and scale index of quality of life of seniors living in nursing home residents. 788 were identified elderly welcomed with women (78%), black race (57%), at the age of 80 years or more with (54%), singles (62%), with incomplete basic education (53%) and elderly dependents for basic daily life activities (46%), with 53.0% are welcomed for over four years. There are three sizes of nursing homes: small (22.7%), medium (40.9%) and large (36.4%) and half has dormitories with up to three beds. It was found that elderly 395 had preserved cognitive capacity and 347 of them were included in the evaluation of quality of life. The highest quality scores were assigned by elderly female, with 90 years or more, higher education, independent, resident in institutions, providing dormitory for four people, with room for individual assistance, external area for recreation and accessibility routes. The study reinforces the need to identify factors that promote better adaptation of the institutionalized elderly and meet the demands that contribute to your quality of life; encouraging the effective participation of the family and the development of activities in the interests of the elderly. It becomes imperative to intersectoral articulation of public policies of Health and Social Services, because these are the main demand policies, mainly on account of dependence by these elderly people. The State needs to assume your responsibility in the implementation of this service.